Pengaruh Ekspetasi, Instrumentalitas, dan Nilai Terhadap Penggunaan Transportasi Umum di Kota Surabaya - Graceshiva Sarrani; Yusuf Hariyoko; Wahid Hidayat (Faculty of Social and Political Science, 2026)
Traffic congestion in Surabaya City has continued to increase due to the growth of private vehicle ownership, prompting the government to develop public transportation as an alternative mode of mobility for the community. The use of public transportation is influenced not only by service availability but also by users’ motivational factors. This study aims to analyze the effects of expectancy, instrumentality, and valence on public transportation usage in Surabaya City. The research employed a quantitative method with a survey approach involving 384 respondents who were users of Surabaya Bus and WiraWiri services, selected through purposive sampling. Data were collected using questionnaires and analyzed through multiple linear regression with the assistance of SPSS software. The results indicate that expectancy has a significant effect on public transportation usage, and instrumentality also has a significant effect, while valence does not have a significant effect on public transportation usage. Simultaneously, expectancy, instrumentality, and valence have a significant effect on public transportation usage. The study concludes that public expectations regarding service quality and the tangible benefits gained from using public transportation are important factors that encourage the use of public transportation in Surabaya City. These factors can help reduce dependence on private vehicles and contribute to alleviating traffic congestion.